Multilevel models for norms in consumer acceptability surveys - Bangos, Cathy Cutad
Abstract (Assessment of concept or product, decision-making, budgeting, and innovative strategies in market research benefit from the comparison of survey scores of some attributes to norms. Multilevel models are used to estimate norms from consumer acceptability surveys. Random coefficient model at project level is the most optimal among class explored based on AIC).